Determinant factors of tax avoidance In Manufacturing Companies on the Indonesian Stock Exchange - Fitriani Saragih (International Journal Of Economics Social And Technology, 2022)
This study aims to determine the determinants of the occurrence of tax avoidance which includes several factors. The factors studied include corporate social responsibility, executive risk preference, and capital intensity in Food and Beverage Companies Listed on the Indonesia Stock Exchange. The population includes all food and beverage companies listed on the IDX with a population of 26 companies with a sample of 8 companies for 6 years of observation. The analytical technique used in this research is Multiple Linear Regression analysis. The results show that Corporate Social Responsibility partially has no effect on Tax Avoidance, Executive Risk Preference partially affects Tax Avoidance, Capital Intensity partially has no effect on Tax Avoidance, and Simultaneously shows that Corporate Social Responsibility, Executive Risk Preference, and Capital Intensity have an effect Significantly on Tax Avoidance in Manufacturing Companies in the Food and Beverage Sector Listed on the Indonesia Stock Exchange